Clusters in System of Instruments of Territorial Development of the Russian Federation - Mindlin, Yurii B.; Kolpak, Eugeny P.; Gasratova, Natalya A. (International Review of Management and Marketing, 2016)
The idea of application of clusters as an instrument of territorial development of the Russian Federation enjoys wide popularity both on regional and federal levels that found the embodiment in formation of a number of the territorial economic structures which are officially referred to clusters. The purpose of this article is to determine whether the territorial economic structures being actively introduced in Russia nowadays can be referred to clusters. The analysis allowed to reveal the main types of the territorial economic structures created in Russia and to describe their distinctive features. Studying the territorial structures created in Russia shows that they can’t be referred to clusters owing to basic discrepancy of the mechanism of their formation and the model of clusters emergence and development. Keywords: clusters, territorial managing structures, hybrids JEL Classifications: M5; P25; P48; R1